Study of arsenic resonance spectral lines in far UV region from a HFEDL for usage in Zeeman absorption spectroscopy. Issue 1 (1st January 2023) - Zorina, Natalja; Abola, Anda; Skudra, Atis; Revalde, Gita
Abstract: This work is focused on obtaining and analyzing the main spectral characteristics of a high-frequency electrodeless light source filled with arsenic for use in high-precision atomic absorption analyzers. We analyzed the relative intensities of the three arsenic resonance spectral lines 189.0 nm, 193.7 nm, and 197.3 nm in the far UV spectral region, the dependence of the intensity on the applied voltage, the impact of the instrumental function on the emission spectra, the influence of self-absorption and the stability of the radiation. Among others, a deconvolution procedure was implemented to obtain the real shapes of the emitted profiles.